Pemikiran Tasawuf Jalan Nabi-Nabi Perspektif Hussien bin Abdul Latiff Singapore - Tiyono, Agus; Putra, Yusdeka (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This article attempts to uncover and elaborate on the perspective of Hussien bin Abdul Latiff Singapore on the tasawuf jalan nabi-nabi or the Sufi path of the prophets. The tasawuf jalan nabi-nabi emphasizes Awaluddin Makrifatullah, which is the beginning of religion in knowing Allah SWT. This is in accordance with the message of the Prophet Muhammad (peace be upon him) to his companions to invite the Jews to believe in Allah and after introducing them to Allah SWT (makrifatullah), to inform them that the five daily prayers are obligatory. Since it is important for a person to know their Lord before worshiping Him, Allah SWT in the primordial world has introduced our souls to Him. Allah SWT did so in order for a person not to say that they do not worship Him because they do not know Him, or they worship Him because of their ancestors' religion. The research method used in this article is library research or literature review, which includes books and scientific journals related to the main research topic. The nature of this article is descriptive analysis with a normative theoretical approach. Based on the findings presented here, the discussion suggests that contemporary Islamic preaching in most Muslim countries promotes certain schools of thought, such as Wahhabi, Salafi, Maliki, Shia, Shafi'i, Hanafi, and Hambali. The correct preaching should be Awaluddin Makrifatullah, which is the same method used by all prophets and messengers to introduce their people to the One God and to worship Him. Thus, the verse